O papel do professor colaborador nos estágios curriculares supervisionados no curso de educação física - Pereira, Juliana Aparecida (2021)
The Supervised Curricular Internship (ECS) is a privileged moment in which future teachers have the possibility to articulate theory and practice, once there is the insertion in the field. This period will provide trainees with experiences in the context of their future profession. In this sense, the Higher Education Institutions (IES) and the field schools need to develop an articulated work that contributes to teacher education, allowing them to move between these different spaces. The teacher who receives the trainee in the school is a central figure in this process because he or she is the one who monitors the students in the school. Thus, the purpose of this study was to understand the role of the teacher-collaborator in the training of Physical Education teachers at a public university in the countryside of São Paulo, within the ECS. The qualitative exploratory-descriptive research had as techniques of data collection the semi-structured interview with 5 trainees and 5 collaborating teachers and the documental analysis of the reports of the subject of ECS produced by the 5 interviewed students. The data analysis was done by means of content analysis, which involved three stages: data ordering, data classification, and final analysis. From the analysis emerged the first axis "The university and school partnership in the internships" in which the IES and the school have a role to be developed in the internships, which reflects on the training of future teachers. The partnership between these two institutions in initial training is fundamental for the understanding and development of this role, and the school is now recognized as a training location. The second axis "Knowledge of the teacher-collaborator" presents the teacher-collaborator who works in the school as an essential figure for the internships, because through his actions and guidance he inserts and helps future teachers in their professional field, mobilizing knowledge from his experience. In this scenario, it is evident the need for the recognition of the teacher-collaborator as a trainer in the context of the internships, requiring training to develop this role, which can be carried out through a partnership between IES and schools. We conclude that the cooperating teacher has a significant role in the internships, since he/she is a co-trainer of future teachers and, in view of this, the need for actions that involve the partnership between university and schools in the direction of promoting continuous training of these professionals.